Long Range Endocrine Delivery of Circulating miR-210 to Endothelium Promotes Pulmonary Hypertension. Issue 5 (14th August 2020) - Zhao, Jingsi; Florentin, Jonathan; Tai, Yi-Yin; Torrino, Stéphanie; Ohayon, Lee; Brzoska, Tomasz; Tang, Ying; Yang, Jimin; Negi, Vinny; Woodcock, Chen-Shan Chen; Risbano, Michael G.; Nouraie, Seyed Mehdi; et al.
Abstract : Rationale: Unproven theories abound regarding the long-range uptake and endocrine activity of extracellular blood-borne microRNAs into tissue. In pulmonary hypertension (PH), microRNA-210 (miR-210) in pulmonary endothelial cells promotes disease, but its activity as an extracellular molecule is incompletely defined. Objective: We investigated whether chronic and endogenous endocrine delivery of extracellular miR-210 to pulmonary vascular endothelial cells promotes PH. Methods and Results: Using miR-210 replete (wild-type [WT]) and knockout mice, we tracked blood-borne miR-210 using bone marrow transplantation and parabiosis (conjoining of circulatory systems). With bone marrow transplantation, circulating miR-210 was derived predominantly from bone marrow. Via parabiosis during chronic hypoxia to induce miR-210 production and PH, miR-210 was undetectable in knockout-knockout mice pairs. However, in plasma and lung endothelium, but not smooth muscle or adventitia, miR-210 was observed in knockout mice of WT-knockout pairs. This was accompanied by downregulation of miR-210 targets ISCU (iron-sulfur assembly proteins)1/2 and COX10 (cytochrome c oxidase assembly protein-10), indicating endothelial import of functional miR-210. Via hemodynamic and histological indices, knockout-knockout pairs were protected from PH, whereas knockout mice in WT-knockout pairs developed PH. In particular, pulmonary vascular engraftment of miR-210–positive interstitial lung macrophages was observed in knockout mice of WT-knockout pairs. To address whether engrafted miR-210–positive myeloid or lymphoid cells contribute to paracrine miR-210 delivery, we studied miR-210 knockout mice parabiosed with miR-210 WT; Cx3cr1 knockout mice (deficient in myeloid recruitment) or miR-210 WT; Rag1 knockout mice (deficient in lymphocytes). In both pairs, miR-210 knockout mice still displayed miR-210 delivery and PH, thus demonstrating a pathogenic endocrine delivery of extracellular miR-210. Conclusions: Endogenous blood-borne transport of miR-210 into pulmonary vascular endothelial cells promotes PH, offering fundamental insight into the systemic physiology of microRNA activity. These results also describe a platform for RNA-mediated crosstalk in PH, providing an impetus for developing blood-based miR-210 technologies for diagnosis and therapy in this disease. Abstract : Supplemental Digital Content is available in the text.